Identification of the Key Parameters for Horizontal Transition Dipole Orientation in Fluorescent and TADF Organic Light‐Emitting Diodes. Issue 37 (2nd August 2021) - Tenopala‐Carmona, Francisco; Lee, Oliver S.; Crovini, Ettore; Neferu, Ana M.; Murawski, Caroline; Olivier, Yoann; Zysman‐Colman, Eli; Gather, Malte C.
Abstract: In organic light‐emitting diodes (OLEDs), horizontal orientation of the emissive transition dipole moment (TDM) can improve light outcoupling efficiency by up to 50% relative to random orientation. Therefore, there have been extensive efforts to identify drivers of horizontal orientation. The aspect ratio of the emitter molecule and the glass‐transition temperature ( T g ) of the films are currently regarded as particularly important. However, there remains a paucity of systematic studies that establish the extent to which these and other parameters control orientation in the wide range of emitter systems relevant for state‐of‐the‐art OLEDs. Here, recent work on molecular orientation of fluorescent and thermally activated delayed fluorescent emitters in vacuum‐processed OLEDs is reviewed. Additionally, to identify parameters linked to TDM orientation, a meta‐analysis of 203 published emitter systems is conducted and combined with density‐functional theory calculations. Molecular weight (MW) and linearity are identified as key parameters in neat systems. In host–guest systems with low‐MW emitters, orientation is mostly influenced by the host T g, whereas the length and MW of the emitter become more relevant for systems involving higher‐MW emitters. To close, a perspective of where the field must advance to establish a comprehensive model of molecular orientation is given. Abstract : Horizontal emitter orientation can significantly increase the efficiency of organic light‐emitting diodes. Intense research over the past decade has provided a large amount of data on the factors that may drive horizontal orientation of organic emitters. This research is reviewed, and a meta‐analysis of the data is combined with quantum‐chemical calculations to identify key parameters that influence this orientation.